2008
DOI: 10.1080/10548400802092742
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effects of Film and Television on Tourism to Screen Locations: A Theoretical and Empirical Perspective

Abstract: It is generally believed that consumption of film and television products can induce tourism to destinations featured. We review the literature relating to this, examine it from the perspective of mass communications theory and develop a general causal model to measure the influence of screen products on visitor numbers. The model is quantified by way of a survey at two popular UK destinations. Our conclusions are that the contributions of screen products to visitor numbers are fractional, diffuse and substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 18 publications
(12 reference statements)
0
29
0
3
Order By: Relevance
“…Much of the existing research on filminduced tourism has measured the impact of media productions on people's perceptions of places while also determining the nature and extent to which these images shape the travel decisions and experiences of tourists (e.g., Young and Young 2008;Hahm and Wang 2011;Hudson et al 2011). Underlying many of these studies is the belief that film tourism can significantly benefit local economies, increase publicity and recognition of destinations, expand infrastructure, and revitalize communities.…”
Section: Such a Perspective Offers A Fuller Recognition Of The Materimentioning
confidence: 99%
“…Much of the existing research on filminduced tourism has measured the impact of media productions on people's perceptions of places while also determining the nature and extent to which these images shape the travel decisions and experiences of tourists (e.g., Young and Young 2008;Hahm and Wang 2011;Hudson et al 2011). Underlying many of these studies is the belief that film tourism can significantly benefit local economies, increase publicity and recognition of destinations, expand infrastructure, and revitalize communities.…”
Section: Such a Perspective Offers A Fuller Recognition Of The Materimentioning
confidence: 99%
“…However, in assessing the economic contribution to the country's well-being created by the film industry, it is worth to look at the film production services sector. There are numerous studies that showed how greatly foreign film production contributes to local economy (Oxford Economics 2010Economics , 2012young, A. F., young, R. 2008;UNESCO 2014;Screen Digest 2006), but a successful film production services sector is beneficial in other ways, also. The current Lithuanian film professionals have been trained precisely by foreign producers working in lithuania.…”
Section: The Value and Importance Created By The Film Industrymentioning
confidence: 99%
“…2 Therefore, the 21st century film industry is well documented as a segment of the creative industries, creating economic capital and contributing to the economy (Griswold 2003;young, A. F., young, R. 2008;Oxford Economics 2010higson 1995;UNESCO 2014;mitkus 2011b;UNCtAD 2004;De Vany 2004;howkins 2001;Florida 2002;European Commission 2010Visser 2014). What matters is that the film industry positively influences related segments of the creative industries, such as tV and advertising (Oxford Economics 2010), and even has a strong impact on the growth of tourism (heitmann 2010;Beeton 2001;Busby, klug 2001).…”
Section: The Value and Importance Created By The Film Industrymentioning
confidence: 99%
“…Film tourists are those who are traveling to a film/drama site as part of their itinerary during their trip. However, non-film tourists are those who are the general tourists without the purpose of visiting a film/drama site [16], [17]. In the current study context, in order to compare the differences between film and non-film tourists, Chinese tourists were divided into film tourists and non-film tourists.…”
Section: A Film-induce Tourismmentioning
confidence: 99%
“…Reference [16] categorized tourists into "film and non-film tourists". Film tourists are those who are traveling to a film/drama site as part of their itinerary during their trip.…”
Section: A Film-induce Tourismmentioning
confidence: 99%